Structural and optical characterisation of Eu implanted AlxGa1-xN - Lorenz, K. (2007)
AlxGa1−xN films grown on sapphire substrates with AlN contents from 0 to 100% were implanted with 8 × 1014 at/cm2 Eu ions. The structural properties and damage accumulation were studied by Rutherford backscattering and channelling spectrometry. The implantation damage decreases considerably for all samples containing Al with AlN showing the best radiation hardness. Despite a high damage level, the fraction of Eu incorporated in near-substitutional sites is highest for GaN. Photoluminescence spectra after annealing at 1100 °C show Eu related luminescence lines in the red spectral region for all samples. The PL intensity at room temperature increases strongly when the AlN content is increased from 0 to 30% and drops steeply for higher AlN contents.